2022
DOI: 10.3390/life13010030
|View full text |Cite
|
Sign up to set email alerts
|

Photon- and Proton-Mediated Biological Effects: What Has Been Learned?

Abstract: The current understanding of the effects of radiation is gradually becoming broader. However, it still remains unclear why some patients respond to radiation with a pronounced positive response, while in some cases the disease progresses. This is the motivation for studying the effects of radiation therapy not only on tumor cells, but also on the tumor microenvironment, as well as studying the systemic effects of radiation. In this framework, we review the biological effects of two types of radiotherapy: photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 117 publications
(147 reference statements)
0
4
0
1
Order By: Relevance
“…As demonstrated in some studies, PT not only has dosimetric advantages, but also favorable profiles of treatment-related toxicity ( 24 ). In our study, acute radiation toxicity was typically represented by grade 1-2 local mucositis and grade 1-2 dermatitis.…”
Section: Discussionmentioning
confidence: 98%
“…As demonstrated in some studies, PT not only has dosimetric advantages, but also favorable profiles of treatment-related toxicity ( 24 ). In our study, acute radiation toxicity was typically represented by grade 1-2 local mucositis and grade 1-2 dermatitis.…”
Section: Discussionmentioning
confidence: 98%
“…Lupu-Plesu et al (2017) presented a comparative analysis of proton and photon therapies on lymphangiogenesis, inflammation and proliferative responses in head and neck squamous cell carcinoma models [88]. The convincing evidence on the biological benefits of PT may have profound clinical implications [89,90]. The clinical use of PT is steadily gaining momentum with the building of new proton centers around the globe, which ensures more facile recruitment of patients into study groups [91].…”
Section: Proton Therapymentioning
confidence: 99%
“…Proton therapy (PT) offers advantages over XRT because it can deliver an optimal radiation dose with precision to tumors while sparing the surrounding normal tissues, thus resulting in less treatment-related toxicity with comparable treatment response and disease-free survival [ 3 , 6 , 7 ]. However, a knowledge gap exists not only in the presumed biological advantage of PT over XRT, but also in the molecular and cellular effects of PT on anti-tumor immune responses [ 8 , 9 ]. Anti-tumor immune responses are of particular interest because of the recent success of immunotherapy in patients with advanced and/or unresectable HNSCC, resulting in full resolution of the disease in some instances, albeit in a small percentage of patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that PT induces a markedly variable and favorable biological response in terms of gene and protein expression in target tissues compared to XRT. PT inhibits factors that contribute to angiogenesis, inflammation, and DNA damage and favors tumor development and growth, while XRT increases these factors [ 3 , 6 , 8 , 12 , 13 ]. Furthermore, transcriptomic studies in murine models of colon cancer have shown that PT activates anti-tumor immune response pathways [ 9 ].…”
Section: Introductionmentioning
confidence: 99%